PENGEMBANGAN MODEL SOCIOCULTURE-BASED NARRATIVE UNTUK KOMPETENSI MENULIS MATA KULIAH BAHASA INGGRIS DI PGSD - Ali Mustadi (Faculty of Languages and Arts, Universitas Negeri Yogyakarta, 2014)
This study aims to produce a Socioculture-Based Narrative model for the writing skillbased on communicative competence in the English subject at PGSD. This was a researchand development study employing the model by Borg Gall consisting of four stages,i.e.: exploration, model development and expert judgment, model tryout, and validation.The results are as follows. First, the developed model has taken into account of thefour communicative competence aspects, i.e.: grammatical competence, sociolinguisticcompetence, discourse competence, and strategic competence. Second, based on expertjudgment, the developed learning design is appropriate to improve PGSD students’writing skill. Third, the results of the product tryout show that the design is effective toimprove students’ writing skill. Fourth, the results of the t-test show a significant positiveeffect of the application of the developed model on the improvement of PGSD students’narrative writing skill.